Study Habits of CS 1 Students: What Do They Say They Do? - Sheard, J.; Carbone, A.; Chinn, D.; Laakso, M. (2013 Learning and Teaching in Computing and Engineering (LaTiCE), 2013)
With the growing use of the Web in university education, increasingly student learning activity is happening outside of the classroom. Consequently it is becoming more and more difficult for teachers to know how their students are going about the learning process. This is of particular concern for the teaching of programming as students typically find this task hard and programming courses often experience high dropout rates. The aim of our research was to explore the study habits of introductory programming students to discover what motivates them to engage in particular activities and use particular resources, and what activities and resources they find valuable for their learning. Twelve introductory programming students were interviewed using a semi-structured interview protocol. From our study we gained a holistic understanding of the students' journeys in learning programming during their introductory programming course. A key finding was that the classroom experience is no longer central to students' learning. Many students had abandoned textbooks and other teacher-provided resources and are heavily reliant on the internet as source of help and of learning.